Barriers to patient recruitment in a poststroke neurorehabilitation multicenter trial in Brazil - da Silva, T. R. [UNESP]; Luvizutto, G. J.; Martins, L. G. [UNESP]; da Costa, R. D.M. [UNESP]; de Souza, J. T. [UNESP]; Winckler, F. C. [UNESP]; Sartor, L. C.A. [UNESP]; Modolo, G. P. [UNESP]; Ferreira, N. C. [UNESP]; Rodrigues, J. C.S. [UNESP]; Kanda, R. G. [UNESP]; Fogaroli, M. O. [UNESP]; et al. (FapUNIFESP (SciELO), 2023)
There is a high demand for stroke rehabilitation in the Brazilian public health system, but most studies that have addressed rehabilitation for unilateral spatial neglect (USN) after stroke have been performed in high-income countries. Therefore, the aim of this study was to analyze USN patient recruitment in a multicenter noninvasive brain stimulation clinical trial performed in Brazil and to provide study design recommendations for future studies. We evaluated the reasons for exclusion of patients from a multicenter, randomized, double-blinded clinical trial of rehabilitation of USN patients after stroke. Clinical and demographic variables were compared between the included and excluded patients. A descriptive statistical analysis was performed. Only 173 of the 1953 potential neglect patients (8.8%) passed the initial screening. After screening evaluation, 87/173 patients (50.3%) were excluded for clinical reasons. Cognitive impairment led to the exclusion of 21/87 patients (24.1%). Low socioeconomic status led to the exclusion of 37/173 patients (21.4%). Difficulty obtaining transportation to access treatment was the most common reason for their exclusion (16/37 patients, 43.3%). The analyzed Brazilian institutions have potential for conducting studies of USN. The recruitment of stroke survivors with USN was restricted by the study design and limited financial support. A history of cognitive impairment, intracranial stenting or craniectomy, and lack of transportation were the most common barriers to participating in a multicenter noninvasive brain stimulation trial among patients with USN after stroke.
Keywords: Clinical trial; Rehabilitation; Stroke; Transcranial direct current stimulation; Unilateral spatial neglect